Germany : Technical Note on Stress Testing. (IMF Staff Country Reports; Country Report ;, 2011)
This note summarizes the stress tests undertaken for the German banking system as part of the Financial Sector Assessment Program (FSAP) update. Solvency tests for the German banking system assessed medium-term vulnerabilities under two adverse macroeconomic scenarios. The tests considered a variety of measures of soundness, and took into account funding costs, sovereign risk, upcoming changes in the regulatory rules, and behavioral changes of banks. The test results revealed that German banks are robust against many shocks, and that important vulnerabilities still remain.